BKB Program Optimization: Effectiveness of Cadre Role, Implementation Barriers, and Increased Parental Participation: Optimalisasi Program BKB : Efektivitas Peran Kader, Hambatan Pelaksanaan, dan Peningkatan Partisipasi Orangtua - Mauludiyah, Yully Riska; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2024)
This qualitative study aims to analyze the role of cadres in the Bina Keluarga Balita (BKB) program in Jerukpurut Village, Gempol District, Pasuruan Regency, as well as to identify the inhibiting factors affecting the program's activities. The study utilized purposive sampling for informant selection and employed interviews, observation, and documentation as data collection techniques. The results revealed that BKB cadres' roles were suboptimal, with factors such as cost and time constraints, double duties, and low mother participation hindering the program's activities. The implication of this study underscores the need for addressing the identified inhibiting factors to enhance the effectiveness of the BKB program in promoting parental knowledge and child development in the community. Highlight : The study analyzes the role of cadres in the Bina Keluarga Balita (BKB) program in Jerukpurut Village, Gempol District, Pasuruan Regency. The study identifies inhibiting factors affecting the program's activities, such as cost and time constraints, double duties, and low mother participation. The study underscores the need for addressing the identified inhibiting factors to enhance the effectiveness of the BKB program in promoting parental knowledge and child development in the community. Keywords: Bina Keluarga Balita, cadres, inhibiting factors, parental knowledge, child development.